Respuesta agronómica de dos variedades de maní (Arachis hypogaea L.) a tres marcos de plantación en la zona de Mocache - Pallo Caicedo, Ricardo Alonso (2021)
The plantation frameworks have a determining effect on the development and production of crops, such as peanuts. Considering this, the present investigation had the general objective of evaluating the agronomic response of two varieties of peanuts (Arachis hypogaea L.) to three plantation frames in the Mocache zone. The test was carried out on the grounds of the Quinta Rosa Esther owned by Mr. Pedro Pallo Sevillano, located in the Mocache canton. Two varieties of peanuts were studied: INIAP 381 and INIAP 382, planted in three plantation frames: 0.15 x 0.50 m; 0.20 x 0.50 m and 0.30 x 0.50 m. The results obtained showed that the planting frames did not significantly influence the average days of crop flowering (41.72 days), number of pods per pod (3.5) and weight of 100 seeds (42.78 g), however, the greater spacing Between plants allowed to obtain plants of greater height at 30, 50 and 70 days (25.40, 33.48 and 48.43 cm), with higher yield component values (averages of: 18.33 pods per plant, 3.83 seeds per pod, 69.83 seeds per plant and 27.40 g per plant). Despite the fact that the 0.30x0.50 m plantation frame produced a higher yield per plant in both varieties, a higher yield per hectare could be obtained in the INIAP 381 variety with the 0.15x0.50 m plantation frame (2728.89 kg ha -1), while in the INIAP 382 variety, with the plantation frame of 0.20 x 0.50 m (3195.56 kg ha-1). The comparative analysis between the two peanut varieties showed that the INIAP 382 variety is more productive, producing an average of 2656.30 kg ha-1, as a result of the average production of more pods (18.67) and seeds per plant (64.67)), also producing a higher unit yield (27.47 g). Keywords: Peanut cultivation, growth, production.